Volumetric R2* mapping using z‐shim multi‐echo gradient echo imaging. Issue 3 (24th March 2014) - Han, Dongyeob; Nam, Yoonho; Gho, Sung‐Min; Kim, Dong‐Hyun
<x xml:space="preserve">Abstract</x> Purpose To introduce macroscopic B0 field inhomogeneity‐compensated volumetric R2* mapping method with a three‐dimensional (3D) z‐shim multi‐echo acquisition. Methods The proposed z‐shim sequence acquired conventional and z‐shimmed echoes alternately with bipolar readout gradients. A constant‐valued z‐shim gradient was applied prior to each negative readout gradient lobe. A phase combination algorithm was also proposed based on this pulse sequence, which acquires a B0 inhomogeneity‐compensated field map that was shown to play a critical role for accurate R2* mapping. A modified signal model based on recently suggested model for 3D acquisition was proposed for R2* quantification. Results To validate the performance of the proposed method, phantom and in vivo experiments were performed and compared with other methods. An increase in the range of field inhomogeneity correction was shown in the phantom results. For in vivo studies, the proposed method showed enhanced R2* map quality for the different subjects. Conclusion The proposed method improves R2* estimation, especially in the frontal and temporal regions. Magn Reson Med 73:1164–1170, 2015. © 2014 Wiley Periodicals, Inc.